Antifungal effects of Lactobacillus species isolated from local dairy products - Karami, Sahar; Roayaei, Mohammad; Zahedi, Elnaz; Bahmani, Mahmoud; Mahmoodnia, Leila; Hamzavi, Hosna; Rafieian-Kopaei, Mahmoud (International Journal of Pharmaceutical Investigation)
Objective: The Lactobacillus is a genus of lactic acid bacteria which are regularly rod‑shaped, nonspore, Gram‑positive, heterogeneous, and are found in a wide range of inhabitants such as dairy products, plants, and gastrointestinal tract. A variety of antimicrobial compounds and molecules such as bacteriocin are produced by these useful bacteria to inhibit the growth of pathogenic microbes in the food products. This paper aims to examine the isolation of Lactobacillus from local dairies as well as to determine their inhibition effect against a number of pathogens, such as two fungi: Penicillium notatum and Aspergillus fulvous. Materials and Methods: Twelve Lactobacillus isolates from several local dairies. After initial dilution (10−1–10−3) and culture on the setting, de Man, Rogosa and Sharpe‑agar, the isolates were recognized and separated by phenotypic characteristics and biochemical; then their antifungal effect was examined by two methods. Results: Having separated eight Lactobacillus isolates, about 70% of the isolates have shown the inhabiting areas of antifungus on the agar‑based setting, but two species Lactobacillus alimentarius and Lactobacillus delbrueckii have indicated a significant antifungal effect against P. notatum and A. fulvous. Except bacteriocin, lactic acid, and acetic acid, the inhibitor substance is produced by these bacteria. Conclusion: Given the vitality of Lactobacillus in human health, recognition and isolation of the species producing compound in antagonist to the pathogens existing in the food products can be a helpful and effective step toward maintaining the valuable native Lactobacillus and using them in the dairy industries.
Keywords: Antifungal effects; bacteriocin; dairy products; Lactobacillus